Correlation between ZJU index and hepatic steatosis and liver fibrosis in American adults with NAFLD - Luo, Shuang; Weng, Xiaolu; Xu, Jing; Lin, Hao (Frontiers in Medicine, 2024)
Background ZJU index, a novel calculation combining blood glucose, body mass index (BMI), lipids and liver functions, is closely related with non-alcoholic fatty liver disease (NAFLD). However, the correlation between ZJU index and hepatic steatosis and liver fibrosis has not been reported in the studies. This study aims to examine the correlation between these variables. Methods Data from the 2017–2020 NHANES were collected for a cross-sectional study, to explore the linear relationship between ZJU, liver stiffness measurements (LSM) and controlled attenuation parameters (CAP) with multivariate linear regression models. Restricted cubic spline (RCS) regression and threshold effect analyses were utilized to describe the nonlinear relationship. The correlation in subgroups was analyzed based on race, gender, drinking, age, BMI, diabetes and moderate activities. Results In this population-based study, a total of 2,122 adults aged 18–80 years old with NAFLD were included. According to the multivariate linear regression analysis, ZJU had a significant positive correlation with liver fibrosis (LSM, β = 0.182, 95%CI = 0.154–0.211, p < 0.001) and hepatic steatosis (CAP, β = 2.35, 95%CI = 2.14–2.56, p < 0.001), which was stronger in males. According to the RCS analysis, an inverted L-shaped relationship between ZJU and CAP (inflection point at 60.56) and a J-shaped relationship between ZJU index and LSM (inflection point at 51.27) were observed. Conclusion ZJU had a positive correlation with CAP and LSM in American adults with NAFLD. The findings suggest that ZJU may be a valuable biomarker for assessing the severity of liver fibrosis and hepatic steatosis in individuals with NAFLD.